THE IDENTIFICATION OF PERIMORTEM TRAUMA ON BONES AFTER BURNING PROCESS: A SYSTEMATIC REVIEW - Mudaim, Syarifah; Koesbardiati, Toetik (Jurnal Biosains Pascasarjana, 2024)
Fire is often employed to destroy evidence in criminal cases, posing the challenge for forensic experts and forensic anthropologists in determining the cause of death and the victim's identity. Although soft tissue can be completely burned during the burning process, trauma on bone can persist up to a certain temperature and duration of burning. Detecting trauma on the bones after the burning process is crucial, as it can provide insights into the actual cause of death. Therefore, this study was conducted with the objective of assessing whether the identification of perimortem bone trauma after burning process is feasible through a systematic review of prior research. The finding of this investigation reveal that fracture type, texture, colour, shape, and alterations in bone dimensions can serve as indicators to differentiate between perimortem trauma occurring after the burning process and postmortem trauma resulting from burning.